2004
DOI: 10.1142/s0219199704001380
|View full text |Cite
|
Sign up to set email alerts
|

On Sharp Higher Order Sobolev Embeddings

Abstract: We present an elementary unified and self-contained proof of sharp Sobolev embedding theorems. We introduce a new function space and use it to improve the limiting Sobolev embedding theorem due to Brézis and Wainger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
79
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(82 citation statements)
references
References 17 publications
3
79
0
Order By: Relevance
“…Indeed, there are many mathematicians, e.g., Bastero, Milman, Ruiz, Martín, Pustylnik, who have researched this kind of question and found many meaningful and important results. The first result we get, Theorem 3.5, can be regarded as an extension of Theorem 1.2 and Corollary 1.3 in [11]. The second result is Theorem 3.7, which can be regarded as a generalization of Theorem 3 in [6] in the background of the rearrangement invariant spaces.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Indeed, there are many mathematicians, e.g., Bastero, Milman, Ruiz, Martín, Pustylnik, who have researched this kind of question and found many meaningful and important results. The first result we get, Theorem 3.5, can be regarded as an extension of Theorem 1.2 and Corollary 1.3 in [11]. The second result is Theorem 3.7, which can be regarded as a generalization of Theorem 3 in [6] in the background of the rearrangement invariant spaces.…”
Section: Introductionmentioning
confidence: 71%
“…Hence, by Theorem 3.4, we get that if α X > r/n, α X < 1 (equivalent to the Pcondition in [11]), then…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Following [23] and [26] we shall now construct the range spaces for our generalized Sobolev embedding theorem. Suppose that X and Y are r.i. spaces, and let s ∈ R. We define…”
Section: Some New Function Spacesmentioning
confidence: 99%
“…In [2], [23] it is shown that (1.4) implies the following improvement to the Hansson-Brézis-Wainger-Maz ya 2 limiting version of the Sobolev embedding theorem:…”
Section: Introductionmentioning
confidence: 99%